Tennis elbow: an ultrasonographic study in tennis players. Issue 3 (September 1990) - Maffulli, N; Regine, R; Carrillo, F; Capasso, G; Minelli, S
Abstract : The findings of ultrasound examination at and around the lateral humeral epicondyle in 41 tennis players suffering from so called tennis elbow are reported. Ultrasound examinations were performed with a real time ultrasound machine. The tenderness and functional impairment of tennis elbow may be caused by several different lesions, at times appearing in association. Six ultrasonographic characteristics could be identified: Enthesiopathy The proximal part of the tendon was enlarged and there were echogenicity alterations. Tendonitis The tendon of the extensor carpi radialis brevis was enlarged and areas of dyshomogeneous hypoechogenicity were evident with loss of the normal microscopic waveform structure of the tendon collagen. Peritendonitis A thickening of the peritendonous lining was present. Bursitis A bursa was located on the inferior surface of the tendon of the extensor carpi radialis brevis. Intramuscular haematoma Some circular or ovoid hypoechogenic areas within the muscular substance of the extensor carpi radialis brevis were evident. Mixed lesions These were not correlated with the intensity and the duration of the symptoms. Ultrasonographic examination gives a detailed ++image of the structures involved in the tennis elbow syndrome, confirms the diagnosis, and may be useful in monitoring treatment.